A series of temperature-dependent CdII-complexes containing an important family of N-rich heterocycles from in situ conversion of pyridine-type Schiff base1. Issue 35 (18th April 2015) - Ou, Yan-Jun; Ding, Yu-Jia; Wei, Qin; Hong, Xu-Jia; Zheng, Zhi-Peng; Long, Yu-Hua; Cai, Yue-Peng; Yao, Xiang-Dong
<x xml:space="preserve">Abstract</x> An efficient method for the synthesis of N-rich heterocycles has been systematically explored through solvothermal in situ generation from ligand (L) mediated by Cd2+. Their in situ formation mechanisms and coordination chemistry are investigated.